2017
DOI: 10.1155/2017/8158254
|View full text |Cite
|
Sign up to set email alerts
|

Aloesin Suppresses Cell Growth and Metastasis in Ovarian Cancer SKOV3 Cells through the Inhibition of the MAPK Signaling Pathway

Abstract: Aloesin is an active constituent of the herb aloe vera and plays a crucial role in anti-inflammatory activity, ultraviolet protection, and antibacterium. We investigated the role and possible mechanisms of aloesin in the cell growth and metastasis of ovarian cancer. It was found that aloesin inhibited cell viability and cell clonality in a dose-dependent manner. It arrests the cell cycle at the S-phase and induced apoptosis in SKOV3 cells. In an in vivo experiment, it was observed that aloesin inhibited tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 18 publications
0
37
0
1
Order By: Relevance
“…Hyperactivation of the MAPK/ERK and the PI3K/AKT signaling pathways plays key roles in uncontrolled cell proliferation of ovarian cancer (20,21). The results of the western blotting showed that downregulation of miR-665 decreased the expression of p-ERK1/2 but not p-AKT (Fig.…”
Section: Downregulation Of Mir-665 Inactivates the Mapk/erk Pathway Imentioning
confidence: 96%
See 1 more Smart Citation
“…Hyperactivation of the MAPK/ERK and the PI3K/AKT signaling pathways plays key roles in uncontrolled cell proliferation of ovarian cancer (20,21). The results of the western blotting showed that downregulation of miR-665 decreased the expression of p-ERK1/2 but not p-AKT (Fig.…”
Section: Downregulation Of Mir-665 Inactivates the Mapk/erk Pathway Imentioning
confidence: 96%
“…In ovarian cancer, activation of the Src signaling pathway is crucial for the epithelial-mesenchymal transition (EMT) process and in vivo tumor growth in nude mice (19). Previous studies have demonstrated that Src is associated with the activity of MAPK/ERK signaling and PI3K/AKT signaling in cancer cells, which are pivotal for cell proliferation and survival (20,21). Src kinase signaling inhibitor 1 (SRCIN1) functions as a tumor suppressor via inactivation of Src in cancer (22).…”
Section: Introductionmentioning
confidence: 99%
“…This study observed that siCXCR4/siCXCR7 administration significantly reduced the tumour volume and demonstrated higher tumour inhibitive rates of the SKOV3 cells transplanted mouse Xenograft model. Meanwhile, the tumour angiogenesis, metastasis, and EMTcorrelated molecules [7,21,29], including CD31, MMP-9, VEGF-A, and vimentin, were significantly increased, and E-cadherin was significantly decreased in the tumour tissues of the mouse Xenograft model. However, we did not employ more specific methods (such as western blot assay) to detect CD31, MMP-9, VEGF-A, vimentin, and E-cadherin expressions in tumour tissues, which is a limitation of our study.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the tumour angiogenesis-associated molecule, CD31, and tumour distant metastasis-related molecule [21,29], were also detected in siCXCR4/siCXCR7-administrated SKOV3 cells. We found that CD31 and MMP-9 production was significantly inhibited in the SKOV3 cells undergoing siCXCR4/siCXCR7 administration, which suggests that the siCXCR4/siCXCR7 blocks the tumour angiogenesis by suppressing CD31 and MMP-9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant anthraquinones in aloe gel are aloesin, aloe-emodin (AE), and barbaloin. Aloesin is a potent and selective inhibitor of tyrosinase and exhibits direct inhibitory effects on melanogenesis [13]. However, little is known about the role of aloesin in anticancer activity.…”
Section: Introductionmentioning
confidence: 99%